Policies Affecting Pregnant Women with Substance Use Disorder - Colburn Yu (Voices in Bioethics, 2023)
Photo by 14825144 © Alita Xander | Dreamstime.com ABSTRACT The US government's approach to the War on Drugs has created laws to deter people from using illicit drugs through negative punishment. These laws have not controlled illicit drug use, nor has it stopped the opioid pandemic from growing. Instead, these laws have created a negative bias surrounding addiction and have negatively affected particularly vulnerable patient populations, including pregnant women with substance use disorder and newborns with neonatal abstinence syndrome. This article highlights some misconceptions and underscores the challenges they face as they navigate the justice and healthcare systems while also providing possible solutions to address their underlying addiction. INTRODUCTION Pregnant women with substance use disorder require treatment that is arguably for the benefit of both the mother and the fetus. Some suggest that addiction is a choice; therefore, those who misuse substances should not receive treatment. Proponents of this argument emphasize social and environmental factors that lead to addiction but fail to appreciate how chronic substance use alters the brain’s chemistry and changes how it responds to stress, reward, self-control, and pain. The medical community has long recognized that substance use disorder is not simply a character flaw or social deviance, but a complex condition that requires adequate medical attention. Unfortunately, the lasting consequences of the War on Drugs have created a stigma around addiction medicine, leading to significant treatment barriers. There is still a pervasive societal bias toward punitive rather than rehabilitative approaches to addiction. For example, many women with substance use disorder lose custody of their baby or face criminal penalties, including fines and jail time.[1] These punitive measures may cause patients to lose trust in their physicians, ultimately leading to high-risk pregnancies without prenatal care, untreated substance misuse, and potential lifelong disabilities for their newborns.[2] As a medical student, I have observed the importance of a rehabilitative approach to addiction medicine. Incentivizing pregnant women with substance use disorder to safely address their chronic health issues is essential for minimizing negative short-term and long-term outcomes for women and their newborns. This approach requires an open mind and supportive perspective, recognizing that substance use disorder is truly a medical condition that requires just as much attention as any other medical diagnosis.[3] BACKGROUND The War on Drugs was a government-led initiative launched in 1970 by President Richard M. Nixon with the aim of curtailing illegal drug use, distribution, and trade by imposing harsher prison sentences and punishments.[4] However, it is worth noting that one can trace the roots of this initiative back further. In 1914, Congress enacted the Harrison Narcotics Tax Act to target the recreational use of drugs such as morphine and opium.[5] Despite being in effect for over four decades, the War on Drugs failed to achieve its intended goals. In 2011, the Global Commission on Drug Policy released a report that concluded that the initiative had been futile, as “arresting and incarcerating tens of millions of these people in recent decades has filled prisons and destroyed lives and families without reducing the availability of illicit drugs or the power of criminal organizations.”[6] One study published in the International Journal of Drug Policy in the same year found that funding drug law enforcement paradoxically contributed to increasing gun violence and homicide rates.[7] The Commission recommended that drug policies focus on reducing harm caused by drug use rather than solely on reducing drug markets. Recognizing that many drug policies were of political opinion, it called for drug policies that were grounded in scientific evidence, health, security, and human rights.[8] Unfortunately, policy makers did not heed these recommendations. In 2014, Tennessee’s legislature passed a “Fetal Assault Law,” which made it possible to prosecute pregnant women for drug use during pregnancy. If found guilty, pregnant women could face up to 15 years in prison and lose custody of their child. Instead of deterring drug use, the law discouraged pregnant women with substance use disorder from seeking prenatal care. This law required medical professionals to report drug use to authorities, thereby compromising the confidentiality of the patient-physician relationship. Some avoided arrest by delivering their babies in other states or at home, while others opted for abortions or attempted to go through an unsafe withdrawal prior to receiving medical care, sacrificing the mother's and fetus's wellbeing. The law had a sunset provision and expired in 2016. During the two years this law was in effect, officials arrested 124 women.[9] The fear that this law instilled in pregnant women with substance use disorder can still be seen across the US today. Many pregnant women with substance use disorders stated that they feared testing positive for drugs. Due to mandatory reporting, they were not confident that physicians would protect them from the law.[10] And if a woman tried to stop using drugs before seeking care to avoid detection, she often ended up delaying or avoiding care.[11] The American College of Obstetricians and Gynecologists (ACOG) recognizes the fear those with substance use disorders face when seeking appropriate medical care and emphasizes that “obstetric–gynecologic care should not expose a woman to criminal or civil penalties, such as incarceration, involuntary commitment, loss of custody of her children, or loss of housing.”[12] Mandatory reporting strains the patient-physician relationship, driving a wedge between the doctor and patient. Thus, laws intended to deter people from using substances through various punishments and incarceration may be doing more harm than good. County hospitals that mainly serve lower socioeconomic patients encounter more patients without consistent health care access and those with substance use disorders.[13] These hospitals are facing the consequences of the worsening opioid pandemic. At one county hospital where I recently worked, there has been a dramatic increase in newborns with neonatal abstinence syndrome born to mothers with untreated substance use disorders during pregnancy. Infants exposed to drugs prenatally have an increased risk of complications, stillbirth, and life-altering developmental disabilities. At the hospital, I witnessed Child Protective Services removing two newborns with neonatal abstinence syndrome from their mother’s custody. Four similar cases had occurred in the preceding month. In the days leading up to their placement with a foster family, I saw both newborns go through an uncomfortable drug withdrawal. No baby should be welcomed into this world by suffering like that. Yet I felt for the new mothers and realized that heart-wrenching custody loss is not the best approach. During this period, I saw a teenager brought to the pediatric floor due to worsening psychiatric symptoms. He was born with neonatal abstinence syndrome that neither the residential program nor his foster family could manage. His past psychiatric disorders included attention deficit disorder, conduct disorder, major depressive disorder, anxiety disorder, disruptive mood dysregulation disorder, intellectual developmental disorder, and more. During his hospitalization, he was so violent towards healthcare providers that security had to intervene. And his attitude toward his foster parents was so volatile that we were never sure if having them visit was comforting or agitating. Throughout his hospital course, it was difficult for me to converse with him, and I left every interview with him feeling lost in terms of providing an adequate short- and long-term assessment of his psychological and medical requirements. What was clear, however, was that his intellectual and emotional levels did not match his age and that he was born into a society that was ill-equipped to accommodate his needs. Just a few feet away from his room, behind the nurses’ station, were the two newborns feeling the same withdrawal symptoms that this teenager likely experienced in the first few hours of his life. I wondered how similar their paths would be and if they would exhibit similar developmental delays in a few years or if their circumstance may follow the cases hyped about in the media of the 1980s and 1990s regarding “crack babies.” Many of these infants who experienced withdrawal symptoms eventually led normal lives.[14] Nonetheless, many studies have demonstrated that drug use during pregnancy can adversely impact fetal development. Excessive alcohol consumption can result in fetal alcohol syndrome, characterized by growth deficiency, facial structure abnormalities, and a wide range of neurological deficiencies.[15] Smoking can impede the development of the lungs and brain and lead to preterm deliveries or sudden infant death syndrome.[16] Stimulants like methamphetamine can also cause preterm delivery, delayed motor development, attention impairments, and a wide range of cognitive and behavioral issues.[17] Opioid use, such as oxycodone, morphine, fentanyl, and heroin, may result in neonatal opioid withdrawal syndrome, in which a newborn may exhibit tremors, irritability, sleeping problems, poor feeding, loose stools, and increased sweating within 72 hours of life.[18] In 2014, the American Association of Pediatrics (AAP) reported that one newborn was diagnosed with neonatal abstinence syndrome every 15 minutes, equating to approximately 32,000 newborns annually, a five-fold increase from 2004.[19] The AAP found that the cost of neonatal abstinence syndrome covered by Medicaid increased from $65.4 million to $462 million from 2004 to 2014.[20] In 2020, the CDC published a paper that showed an increase in hospital costs from $316 million in 2012 to $572.7 million in 2016.[21] Currently, the impact of the COVID-19 pandemic on the prevalence of newborns with neonatal abstinence syndrome is unknown. I predict that the increase in opioid and polysubstance use during the pandemic will increase the number of newborns with neonatal abstinence syndrome, thereby significantly increasing the public burden and cost.[22] In the 1990s, concerns arose about the potentially irreparable damage caused by intrauterine exposure to cocaine on the development of infants, which led to the popularization of the term “crack babies.”[23] Although no strong longitudinal studies supported this claim at the time, it was not without merit. The Maternal Lifestyle Study (NCT00059540) was a prospective longitudinal observational study that compared the outcomes of newborns exposed to cocaine in-utero to those without.[24] One of its studies revealed one month old newborns with cocaine exposure had “lower arousal, poorer quality of movements and self-regulation, higher excitability, more hypertonia, and more nonoptimal reflexes.”[25] Another study showed that at one month old, heavy cocaine exposure affected neural transmission from the ear to the brain.[26] Long-term follow up from the study showed that at seven years old, children with high intrauterine cocaine exposure were more likely to have externalizing behavior problems such as aggressive behavior, temper tantrums, and destructive acts.[27] While I have witnessed this behavior in the teenage patient during my pediatrics rotation, not all newborns with intrauterine drug exposure are inevitably bound to have psychiatric and behavioral issues later in life. NPR recorded a podcast in 2010 highlighting a mother who used substances during pregnancy and, with early intervention, had positive outcomes. After being arrested 50 times within five years, she went through STEP: Self-Taught Empowerment and Pride, a public program that allowed her to complete her GED and provided guidance and encouragement for a more meaningful life during her time in jail. Her daughter, who was exposed to cocaine before birth, had a normal childhood and ended up going to college.[28] From a public health standpoint, more needs to be done to prevent the complications of substance misuse during pregnancy. Some states consider substance misuse (and even prescribed use) during pregnancy child abuse. Officials have prosecuted countless women across 45 states for exposing their unborn children to drugs.[29] With opioid and polysubstance use on the rise, the efficacy of laws that result in punitive measures seems questionable.[30] So far, laws are not associated with a decrease in the misuse of drugs during pregnancy. Millions of dollars are being poured into managing neonatal abstinence syndrome, including prosecuting women and taking their children away. Rather than policing and criminalizing substance use, pregnant women should get the appropriate care they need and deserve. I. Misconception One: Mothers with Substance Use Disorder Can Get an Abortion If an unplanned pregnancy occurs, one course of action could be to terminate the pregnancy. On the surface, this solution seems like a quick fix. However, the reality is that obtaining an abortion can be challenging due to two significant barriers: accessibility and mandated reporting. Abortion laws vary by state, and in Tennessee, for instance, abortions are banned after six weeks of gestation, typically when fetal heart rhythms are detected. An exception to this is in cases where the mother's life is at risk.[31] Unfortunately, many women with substance use disorders are from lower socioeconomic backgrounds and cannot access pregnancy tests, which could indicate they are pregnant before the six-week cutoff. If a Tennessee woman with substance use disorder decides to seek an abortion after six weeks, she may need to travel to a neighboring state. However, this is not always a feasible option, as the surrounding states (WV, MO, AR, MI, AL, and GA) also have restrictive laws that either prohibit abortions entirely or ban them after six weeks. Moreover, she may be hesitant to visit an obstetrician for an abortion, as some states require physicians by law to report their patients' substance use during pregnancy. For example, Virginia considers substance use during pregnancy child abuse and mandates that healthcare providers report it. This would ultimately limit her to North Carolina if she wants to remain in a nearby state, but she must go before 20 weeks gestation.[32] For someone who may or may not have access to reliable transportation, traveling to another state might be impossible. Without resources or means, these restrictive laws have made it incredibly difficult to obtain the medical care they need. II. Misconception Two: Mothers with SUD are Not Fit to Care for Children If a woman cannot take care of herself, one might wonder how she can take care of another human being. Mothers with substance use disorders often face many adversities, including lack of economic opportunity, trauma from abuse, history of poverty, and mental illness.[33] Fortunately, studies suggest keeping mother and baby together has many benefits. Breastfeeding, for example, helps the baby develop a strong immune system while reducing the mother’s risk of cancer and high blood pressure.[34] Additionally, newborns with neonatal abstinence syndrome who are breastfed by mothers receiving methadone or buprenorphine require less pharmacological treatment, have lower withdrawal scores, and experience shorter hospital stays.[35] Opioid concentration in breastmilk is minimal and does not pose a risk to newborns.[36] Moreover, oxytocin, the hormone responsible for mother-baby bonding, is increased in breastfeeding mothers, reducing withdrawal symptoms and stress-induced reactivity and cravings while also increasing protective maternal instincts.[37] Removing an infant from their mother’s care immediately after birth would result in the loss of all these positive benefits for both the mother and her newborn. The newborns I observed during my pediatrics rotation probably could have benefited from breastfeeding rather than bottle feeding and being passed around from one nurse to the next. They probably would have cried less and suffered fewer withdrawal symptoms had they been given the opportunity to breastfeed. And even if the mothers were lethargic and unresponsive while going through withdrawal, it would still have been possible to breastfeed with proper support. Unfortunately, many believe mothers with substance use disorder cannot adequately care for their children. This pervasive societal bias sets them up for failure from the beginning and greatly inhibits their willingness to change and mend their relationship with their providers. It is a healthcare provider’s duty to provide non-judgmental care that prioritizes the patient’s well-being. They must treat these mothers with the same empathy and respect as any other patient, even if they are experiencing withdrawal. III. Safe Harbor and Medication-Assisted Treatment Addiction is like any other disease and society should regard treatment without stigma. There is no simple fix to this problem, given that it involves the political, legal, and healthcare systems. Punitive policies push pregnant women away from receiving healthcare and prevent them from receiving beneficial interventions. States need to enact laws that protect these women from being reported to authorities. Montana, for example, passed a law in 2019 that provides women with substance use disorders safe harbor from prosecution if they seek treatment for their condition.[38] Medication-assisted treatment with methadone or buprenorphine is the first line treatment option and should be available to all pregnant women regardless of their ability to pay for medical care.[39] To promote continuity of care, health officials could include financial incentives to motivate new mothers to go to follow-up appointments. For example, vouchers for groceries or enrollment in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) may offset financial burdens and allow a mother to focus on taking care of her child and her recovery. IV. Mandated Substance Abuse Programs Although the number of people sentenced to state prisons for drug related crimes has been declining, it is still alarming that there were 171,300 sentencings in 2019.[40] Only 11 percent of the 65 percent of our nation’s inmates with substance use disorder receive treatment, implying that the other 89 percent were left without much-needed support to overcome their addiction.[41] It is erroneous to assume that their substance use disorder would disappear after a period without substance use while behind bars. After withdrawal, those struggling with substance use disorder may still have cravings and the likelihood of relapsing remains high without proper medical intervention. Even if they are abstinent for some time during incarceration, the underlying problem persists, and the cycle inevitably continues upon release from custody. In line with the recommendations by Global Commission on Drug Policy and the lessons learned from the failed War on Drugs, one proposed change in our criminal justice system would be to require enrollment and participation in assisted alcohol cessation programs before legal punishment. Policy makers must place emphasis on the safety of the patient and baby rather than the cessation of substance use. This would incentivize people to actively seek medical care, restore the patient-physician relationship, and ensure that they take rehabilitation programs seriously. If the patient or baby is unsafe, a caregiver could intervene while the patient re-enrolls in the program. Those currently serving sentences in prisons and jails can treat their substance use disorder through medication assisted treatment, cognitive behavioral therapy, and programs like Self Taught Empowerment and Pride (STEP). Medication assisted treatment under the supervision of medical professionals can help inmates achieve and maintain sobriety in a healthy and safe way. Furthermore, cognitive behavioral therapy can help to identify triggers and teach healthier coping mechanisms to prepare for stressors outside of jail. Finally, multimodal empowerment programs can connect people to jobs, education, and support upon release. People often leave prisons and jail without a sense of purpose, which can lead to relapse and reincarceration. Structured programs have been shown to decrease drug use and criminal behavior by helping reintegrate productive individuals into society.[42] V. Medical Education: Narcotic Treatment Programs and Suboxone Clinics Another proactive approach could be to have medical residency programs register with the Drug Enforcement Administration (DEA) as Narcotic Treatment Programs and incorporate suboxone clinics into their education and rotations. Rather than family medicine, OB/GYN, or emergency medicine healthcare workers having to refer their patients to an addiction specialist, they could treat patients with methadone for maintenance or detoxification where they would deliver their baby. Not only would this educate and prepare the future generation of physicians to handle the opioid crisis, but it would allow pregnant women to develop strong patient-physician relationships. CONCLUSION Society needs to change from the mindset of tackling a problem after it occurs to taking a proactive approach by addressing upstream factors, thereby preventing those problems from occurring in the first place. Emphasizing public health measures and adequate medical care can prevent complications and developmental issues in newborns and pregnant women with substance use disorders. Decriminalizing drug use and encouraging good health habits during pregnancy is essential, as is access to prenatal care, especially for lower socioeconomic patients. Many of the current laws and regulations that policy makers initially created due to naïve political opinion and unfounded bias to serve the War on Drugs need to be changed to provide these opportunities. To progress as a society, physicians and interprofessional teams must work together to truly understand the needs of patients with substance use disorders and provide support from prenatal to postnatal care. There should be advocation for legislative change, not by providing an opinion but by highlighting the facts and conclusions of scientific studies grounded in scientific evidence, health, security, and human rights. There can be no significant change if society continues to view those with substance use disorders as underserving of care. Only when the perspective shifts to compassion can these mothers and children receive adequate care that rehabilitates and supports their future and empowers them to raise their children. - [1] NIDA. 2023, February 15. Pregnant People with Substance Use Disorders Need Treatment, Not Criminalization. https://nida.nih.gov/about-nida/noras-blog/2023/02/pregnant-people-substance-use-disorders-need-treatment-not-criminalization [2] Substance Use Disorder Hurts Moms and Babies. National Partnership for Women and Families. June 2021 [3] All stories have been fictionalized and anonymized. [4] A History of the Drug War. Drug Policy Alliance. https://drugpolicy.org/issues/brief-history-drug-war [5] The Harrison Narcotic Act (1914) https://www.druglibrary.org/Schaffer/library/studies/cu/cu8.html [6] The War on Drugs. The Global Commission on Drug Policy. Published June 2011. https://www.globalcommissionondrugs.org/reports/the-war-on-drugs [7] Werb D, Rowell G, Guyatt G, Kerr T, Montaner J, Wood E. Effect of drug law enforcement on drug market violence: A systematic review. Int J Drug Policy. 2011;22(2):87-94. doi:10.1016/j.drugpo.2011.02.002 [8] Global Commission on Drug Policy, 2011 [9] Women NA for P. Tennessee’s Fetal Assault Law: Understanding its impact on marginalized women - New York. Pregnancy Justice. Published December 14, 2020. https://www.pregnancyjusticeus.org/tennessees-fetal-assault-law-understanding-its-impact-on-marginalized-women/ [10] Roberts SCM, Nuru-Jeter A. Women’s perspectives on screening for alcohol and drug use in prenatal care. Womens Health Issues Off Publ Jacobs Inst Womens Health. 2010;20(3):193-200. doi:10.1016/j.whi.2010.02.003 [11] Klaman SL, Isaacs K, Leopold A, et al. Treating Women Who Are Pregnant and Parenting for Opioid Use Disorder and the Concurrent Care of Their Infants and Children: Literature Review to Support National Guidance. J Addict Med. 2017;11(3):178-190. doi:10.1097/ADM.0000000000000308 [12] Substance Abuse Reporting and Pregnancy: The Role of the Obstetrician–Gynecologist. https://www.acog.org/en/clinical/clinical-guidance/committee-opinion/articles/2011/01/substance-abuse-reporting-and-pregnancy-the-role-of-the-obstetrician-gynecologist [13] R. Ghertner, G Lincoln The Opioid Crisis and Economic Opportunity: Geographic and Economic Trends. ASPE. Office of Assistant Secretary for Planning and Evaluation. DHHS Revised September 11, 2018 https://aspe.hhs.gov/reports/economic-opportunity-opioid-crisis-geographic-economic-trends [14] Midon, M. Z., Gerzon, L. R., & de Almeida, C. S. (2021). Crack and motor development of babies living in an assistance shelter. ABCS Health Sciences, 46, e021215-e021215. And for example, see Crack Babies: Twenty Years Later : NPR https://www.npr.org/templates/story/story.php?storyId=126478643 [15] Williams JF, Smith VC, the Committee on Substance Abuse. Fetal Alcohol Spectrum Disorders. Pediatrics. 2015;136(5):e20153113. doi:10.1542/peds.2015-3113 [16] CDC Tobacco Free. Smoking During Pregnancy. Centers for Disease Control and Prevention. Published April 11, 2022. https://www.cdc.gov/tobacco/basic_information/health_effects/pregnancy/index.htm [17] Abuse NI on D. What are the risks of methamphetamine misuse during pregnancy? National Institute on Drug Abuse. https://nida.nih.gov/publications/research-reports/methamphetamine/what-are-risks-methamphetamine-misuse-during-pregnancy [18] CDC. Basics About Opioid Use During Pregnancy | CDC. Centers for Disease Control and Prevention. Published July 21, 2021. https://www.cdc.gov/pregnancy/opioids/basics.html [19] Honein MA, Boyle C, Redfield RR. Public Health Surveillance of Prenatal Opioid Exposure in Mothers and Infants. Pediatrics. 2019;143(3):e20183801. doi:10.1542/peds.2018-3801 [20] Winkelman TNA, Villapiano N, Kozhimannil KB, Davis MM, Patrick SW. Incidence and Costs of Neonatal Abstinence Syndrome Among Infants with Medicaid: 2004–2014. Pediatrics. 2018;141(4):e20173520. doi:10.1542/peds.2017-3520 [21] Strahan AE, Guy GP Jr, Bohm M, Frey M, Ko JY. Neonatal Abstinence Syndrome Incidence and Health Care Costs in the United States, 2016. JAMA Pediatr. 2020;174(2):200-202. doi:10.1001/jamapediatrics.2019.4791 [22] Ghose R, Forati AM, Mantsch JR. Impact of the COVID-19 Pandemic on Opioid Overdose Deaths: a Spatiotemporal Analysis. J Urban Health Bull N Y Acad Med. 2022;99(2):316-327. doi:10.1007/s11524-022-00610-0 [23] Mayes LC, Granger RH, Bornstein MH, Zuckerman B. The Problem of Prenatal Cocaine Exposure: A Rush to Judgment. JAMA. 1992;267(3):406-408. doi:10.1001/jama.1992.03480030084043 [24] NICHD Neonatal Research Network. The Maternal Lifestyle Study. clinicaltrials.gov; 2016. https://clinicaltrials.gov/ct2/show/study/NCT00059540 [25] Lester BM, Tronick EZ, LaGasse L, et al. The maternal lifestyle study: effects of substance exposure during pregnancy on neurodevelopmental outcome in 1-month-old infants. Pediatrics. 2002;110(6):1182-1192. doi:10.1542/peds.110.6.1182 [26] Lester BM, Lagasse L, Seifer R, et al. The Maternal Lifestyle Study (MLS): effects of prenatal cocaine and/or opiate exposure on auditory brain response at one month. J Pediatr. 2003;142(3):279-285. doi:10.1067/mpd.2003.112 [27] Bada HS, Bann CM, Bauer CR, et al. Preadolescent behavior problems after prenatal cocaine exposure: Relationship between teacher and caretaker ratings (Maternal Lifestyle Study). Neurotoxicol Teratol. 2011;33(1):78-87. doi:10.1016/j.ntt.2010.06.005 [28] N, P, R. Crack Babies: Twenty Years Later. NPR. Published May 3, 2010. https://www.npr.org/templates/story/story.php?storyId=126478643 [29] Miranda L, Dixon V, September CRP on, 30, 2015. How States Handle Drug Use During Pregnancy http://projects.propublica.org/graphics/maternity-drug-policies-by-state [30] NCDAS: Substance Abuse and Addiction Statistics [2023]. NCDAS. https://drugabusestatistics.org/ [31] (Tenn. Code Ann. § 39-15-216). [32] Institute G. Interactive Map: US Abortion Policies and Access After Roe. https://states.guttmacher.org/policies/ [33] Whitesell M, Bachand A, Peel J, Brown M. Familial, Social, and Individual Factors Contributing to Risk for Adolescent Substance Use. J Addict. 2013;2013:579310. doi:10.1155/2013/579310 [34] CDC. Five Great Benefits of Breastfeeding. Centers for Disease Control and Prevention. Published July 27, 2021. https://www.cdc.gov/nccdphp/dnpao/features/breastfeeding-benefits/index.html [35] Welle-Strand GK, Skurtveit S, Jansson LM, Bakstad B, Bjarkø L, Ravndal E. Breastfeeding reduces the need for withdrawal treatment in opioid-exposed infants. Acta Paediatr. 2013;102(11):1060-1066. doi:10.1111/apa.12378 [36] Ilett KF, Hackett LP, Gower S, Doherty DA, Hamilton D, Bartu AE. Estimated dose exposure of the neonate to buprenorphine and its metabolite norbuprenorphine via breastmilk during maternal buprenorphine substitution treatment. Breastfeed Med Off J Acad Breastfeed Med. 2012;7:269-274. doi:10.1089/bfm.2011.0096 [37] Pedersen CA, Smedley KL, Leserman J, et al. Intranasal Oxytocin Blocks Alcohol Withdrawal in Human Subjects. Alcohol Clin Exp Res. 2013;37(3):484-489. doi:10.1111/j.1530-0277.2012.01958.x [38] Montan